2014
DOI: 10.1002/jrs.4624
|View full text |Cite
|
Sign up to set email alerts
|

In‐plane and out‐of‐plane defects of graphite bombarded by H, D and He investigated by atomic force and Raman microscopies

Abstract: International audienceGraphite samples exposed to H, D and He plasma at fluencies from 10(16) to 10(18)cm(-2) have been investigated by means of atomic force and Raman microscopies. The ion energy was varied between 40 and 800eV, and the ion incidence was either perpendicular (Highly Oriented Pyrolitic Graphite) or parallel (carbon/carbon composite) to the basal plane. When increasing the impinging ion energy, the growth of nanometric domes at the surface has been observed by atomic force microscopy and the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 74 publications
(146 reference statements)
0
19
0
Order By: Relevance
“…Among other changes, the increase of the D band width with the pressure increase is more pronounced than for the G band leading to a rapid evolution of the D band width compared to the G band width. This rapid evolution is not seen for implanted graphite samples on which two kinds of signatures (amorphous and nanocrystalline) have been observed together [231]. An explanation may be that a synergetic effect hinders curvature of graphene planes, preferring the formation of sp 3 defects.…”
Section: Other Effects: Our Propositionsmentioning
confidence: 89%
See 2 more Smart Citations
“…Among other changes, the increase of the D band width with the pressure increase is more pronounced than for the G band leading to a rapid evolution of the D band width compared to the G band width. This rapid evolution is not seen for implanted graphite samples on which two kinds of signatures (amorphous and nanocrystalline) have been observed together [231]. An explanation may be that a synergetic effect hinders curvature of graphene planes, preferring the formation of sp 3 defects.…”
Section: Other Effects: Our Propositionsmentioning
confidence: 89%
“…Mallet et al observed such a variation of Г D /Г G with L a , reaching the lowest value at L a = 8 nm (see Figure 13 in the work of Zhao et al [271]). ) (carbon fibers [289], soots [122,290,291], pyrocarbons [123,252,260], nanocones [223], a large variety of disordered carbons collected from the Tore Supra tokamak [66], nanographites from Cançado et al [65], geothermic carbons from [292], and ion implanted graphites taken from [231]). Depending on the characteristic size of the aromatic domain, the data are grouped in three different areas: the lowest rectangle with L a higher than roughly 10 nm, the intermediate region with L a in the range of few to 10 nm, and the higher one with L a close to 1 nm.…”
Section: Role Of Defectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pardanaud and co‐workers described the in‐plane and out‐of‐plane defects of graphite bombarded by H, D and He as investigated by atomic force and Raman microscopies. They found that as the number of vacancies created in the material increases, the number of in‐plane defects decreases to the benefit of the out‐of‐plane defects …”
Section: Solid‐state Studiesmentioning
confidence: 99%
“…They found that as the number of vacancies created in the material increases, the number of in-plane defects decreases to the benefit of the out-of-plane defects. [126] Linear chains and polymers He and Lu carried out an in situ confocal micro-Raman spectroscopic investigation of rearrangement kinetics and phase evolution of ultra-high molecular weight polyethylene during annealing. [127] Liszka and co-workers carried out a Raman micro-spectroscopy investigation of quantitative thickness measurements of nanometer thin polymer films.…”
Section: Single Crystalsmentioning
confidence: 99%